Sunspot variablity and an attempt to predict solar cycle 23 by adaptive filtering - Rangarajan, G.K. (My University, 1998)
The series of annual mean relative sunspot numbers (R z) for 1749–1996 is subjected to the recently developed methodology of Singular Spectrum Analysis (SSA). This technique also enables data-adaptive filtering of the individual spectral components. Low order autoregressive modelling of the components are combined to provide a basis for predicting the solar cycle 23. The R z series is largely dominated by a doublet with periods 11.13 and 10.35 yr. close to the nominal solar cycle periodicity, a longer period variation (~110 yr.) which is the envelope of the amplitude maxima and two clusters of periodicities centred around 8 yr. and 5.5 yr. The solar magnetic cycle has no detectable component. The predicted maximum for cycle 23 will have a magnitude of ~130 and the epoch of maximum is expected between late 2000 A.D. and early 2001 A.D.
Keywords: Predict solar cycle; Relative sunspot numbers; Singular spectrum analysis